2002
DOI: 10.1210/jc.2002-020365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid-Stimulating Hormone Suppression with Levothyroxine in Reducing the Volume of Solitary Thyroid Nodules and Improving Extranodular Nonpalpable Changes: A Randomized, Double-Blind, Placebo-Controlled Trial by the French Thyroid Research Group

Abstract: The efficacy of suppressing TSH secretion with levothyroxine (L-T(4)) in reducing solitary thyroid nodule growth is still controversial. In this prospective multicenter, randomized, double-blind, placebo-controlled trial, 123 patients with a single palpable benign nodule were included and randomly allocated to an 18-month treatment with L-T(4) or placebo. Individual dose was adjusted to allow a serum TSH level below 0.3 mIU/liter. Clinical and ultrasonographic nodule characteristics were assessed before treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
15

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 45 publications
0
41
0
15
Order By: Relevance
“…LT 4 therapy has been prescribed to reduce the size of benign thyroid nodules, but the clinical benefit of a small to modest reduction in size is not clear (142)(143)(144)(145)(146)(147). About a third (30.6%) of euthyroid children had a ‡ 50% reduction in nodule size, which was directly correlated with TSH levels (r = 0.640, p < 0.001) and inversely with LT 4 dose (r = -0.389, p = 0.009) (140).…”
Section: Recommendation Rating: E [B6] How Should Thyroid Nodules Be mentioning
confidence: 99%
“…LT 4 therapy has been prescribed to reduce the size of benign thyroid nodules, but the clinical benefit of a small to modest reduction in size is not clear (142)(143)(144)(145)(146)(147). About a third (30.6%) of euthyroid children had a ‡ 50% reduction in nodule size, which was directly correlated with TSH levels (r = 0.640, p < 0.001) and inversely with LT 4 dose (r = -0.389, p = 0.009) (140).…”
Section: Recommendation Rating: E [B6] How Should Thyroid Nodules Be mentioning
confidence: 99%
“…167 Some studies have reported that L-thyroxine suppressive therapy results in reduction in nodule volume, especially in small ones, [168][169][170][171] whereas others do not support this finding and suggest that patients with cytologically benign nodules are best followed without thyroxine treatment. 165,172 Moreover, in a 10-year retrospective analysis, 13% of histologically (after surgery) proved PTCs had previously shown a decrease in size during suppressive L-thyroxine therapy.…”
Section: 167mentioning
confidence: 99%
“…Kuma et al demonstrated that 23% of single nodule enlarged, but 30% disappeared and the remaining showed no change in size on long-term follow-up for 9-11 years based on palpation [5]. Thereafter, several studies that evaluated tumor size on ultrasonography have been published, showing that 4-22% of nodules showed 50% increase and 0-20% showed 50% decrease in volume [6][7][8][9][10][11][12][13]. However, average follow-up periods were less than 5 years in these stud- ings suggestive of papillary carcinoma with negative cytology, we should consider the possibility of a benign nodule degenerating over time.…”
Section: Discussionmentioning
confidence: 99%